2022
DOI: 10.1186/s12884-022-04588-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of antenatal care visit with utilization of institutional delivery care services in Afghanistan: intersections of education, wealth, and household decision-making autonomy

Abstract: Background The importance of antenatal care (ANC) visits in safe motherhood and childbirth is well-documented. However, less is known how social determinants of health interact with ANC visits in shaping the uptake of professional delivery care services in low-income countries. This study examines the associations of ANC visits with institutional delivery care utilization outcomes in Afghanistan. Further, we assess the extent to which ANC visits intersect with education, wealth, and household d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…We found ANC attendance likely to be associated with delivering in a health structure. Similar studies found that ANC visits are an essential and significant determinant of delivery at a health facility [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 62%
“…We found ANC attendance likely to be associated with delivering in a health structure. Similar studies found that ANC visits are an essential and significant determinant of delivery at a health facility [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 62%
“…This multifaceted intervention successfully encouraged pregnant women’s timely initiation and completion of ANC, and was found to be effective in promoting hospital delivery. Previous research conducted in developing areas demonstrated that women who receive timely and adequate ANC were 2.4–6.8 times more likely to deliver at a healthcare facility compared to those who did not receive ANC [ 23 26 ]. During ANC visits, ANC providers offer advice based on maternal and fetal health, facilitating informed decisions regarding childbirth delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Afghanistan have examined utilization of maternal healthcare and the associated in uential factors in recent years (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Of these, one study found that sociodemographic and cultural (woman's role in making the decision to seek PNC service) factors were associated with the utilization of PNC visits (12).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, one study found that sociodemographic and cultural (woman's role in making the decision to seek PNC service) factors were associated with the utilization of PNC visits (12). Three studies reported that sociodemographic and cultural factors were associated with institutional deliveries or skilled birth attended deliveries (13,14,18). One of the three studies reported that women who had at least four ANC visits were more likely to give birth in a health facility or with skilled birth attendants than those who had none, and women from higher socioeconomic status used institutional deliveries more than women from lower socioeconomic status (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation